(untitled) (Journal of Nepal Geological Society, 1998)
Structural analysis reveals that the Central Crystallines in the Garhwal region were subjected to four phases of deformations (D1 to D4). The D1 deformational phase is highly obliterated and usually found as F1 intrafolial (rootless) tight isoclinal folds in migmatites and gneisses. The D2 deformational phase produced strong pervasive S2 schistosity and asymmetric and open fold (F2) plunging 20-30° towards ENE-WSW. The L2 lineation plunge 5-10° towards east-west is well developed in medium grade metamorphic rocks. The D1 deformations were responsible for F3 folds reflected in large scale anticlinal and synclinal, overturned and recumbent folds, which have 10-40° plunges towards NW. The late D3 deformational stresses were responsible for shearing along the middle limbs of F1 folds and they ultimately initiated thrusting. The NNE SSW plunging mineral or stretching lineation (L3), S3 crenulation cleavage and S-C fabrics were developed during the dominant ductile shearing related to the late D3 deformation. The D4 phase characterised by brittle-ductile deformation (minor kinks, puckers, transverse/transcurrent faults, and S-C’ fabrics) and extensive cataclasis along thrust- and fault-zones reflects the last episode of deformation. The structural and geochronological data indicate that D1 and D2 deformation episodes may be related to the Precambrian time while D3 and D4 are exclusively of the Tertiary age.